PENGARUH TEKNIK SELF MANAGEMENT UNTUK MENURUNKAN PERILAKU MEROKOK SISWA KELAS IX SMP NEGERI 40 PEKANBARU MELALUI BIMBINGAN KELOMPOK - Irfan Satria; Syahrilfuddin Syahrilfuddin; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effects of self management techniques to reduce smoking behavior of class IX students of SMPNegeri 40 Pekanbaru through group guidance. This type of research is a quantitatiative study with an experimental metohod using the design on the one-group pretest – posttest design. The measuring instrument used in this study is a smoking behavior measurement scale consisting of 55 items before validation and after validation there are 47 item valid, with validity of 0.5255 and reliability of 0.918. Determination of the subject was obtained from the BK teacher’s recommendations and student case book data. The data analysis technique used is non-parametric statiscal techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. This is known from "Test Statistics", known as Asymp. Sig. (2-tailed) worth 0.017. Because the value of 0.017 is smaller than <0.05, it can be concluded that "Ha is accepted". For this reason, it can be concluded that there are differences in the score of smoking behavior before and after treatment given in the from of self management techniques. Based on the calculation that have been made, the 100% pre-test is in the high category. Post-test 100% in the medium category. Thus Ha is accepted and Ho is rejected. So that it can be concluded that the technique of self management can reduce the smoking behavior of students of SMPNegeri 40 Pekanbaru.Key Words: Students of SMP, Self Management, The Smoking Beh avior